2015
DOI: 10.1111/resp.12704
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of procalcitonin in pneumonia: A systematic review and meta‐analysis

Abstract: This meta‐analysis was performed to determine the accuracy of procalcitonin (PCT) in predicting mortality in pneumonia patients with different pathogenic features and disease severities. A systematic search of English‐language articles was performed using PubMed, Embase, Web of Knowledge and the Cochrane Library to identify studies. The diagnostic value of PCT in predicting prognosis was determined using a bivariate meta‐analysis model. The Q‐test and I 2 index were used to test heterogeneity. A total of 21 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 47 publications
5
49
0
3
Order By: Relevance
“…found that PCT levels at admission were moderately accurate in identifying the outcome in septic patients, with 51% sensitivity and an AUC of 0.6737. Additionally, a recent meta-analysis showed that the commonly used cut-off for PCT of 0.5 ng/mL only had a sensitivity of 44% to identify patients with pneumonia who have a high risk of death38. The meta-analysis performed by Su et al .…”
Section: Discussionmentioning
confidence: 99%
“…found that PCT levels at admission were moderately accurate in identifying the outcome in septic patients, with 51% sensitivity and an AUC of 0.6737. Additionally, a recent meta-analysis showed that the commonly used cut-off for PCT of 0.5 ng/mL only had a sensitivity of 44% to identify patients with pneumonia who have a high risk of death38. The meta-analysis performed by Su et al .…”
Section: Discussionmentioning
confidence: 99%
“…First described as a biomarker for sepsis in 1993 [62], procalcitonin has since been validated repeatedly as not only a marker of bacterial infection, but also a correlate of severity in sepsis and septic shock [63]. A meta-analysis of 21 studies including over 6000 patients showed that an elevated procalcitonin level was a risk factor for mortality (RR 4.38) [64]. A review of 1770 patients with CAP showed that procalcitonin levels had an approximately linear association with the need for invasive respiratory or vasopressor support; at levels >10 ng/mL, the risk was 22.4% compared to 4% in patients with procalcitonin <0.05 ng/mL [65].…”
Section: Procalcitoninmentioning
confidence: 99%
“…The PCT was the most extensively studied in a total of 21 studies with 6007 pneumonia patients. Although elevated PCT level was a risk factor for death in CAP, particularly patients with a low CURB-65 score, the commonly used cutoff, 0.5 ng/mL, had low sensitivity in identifying patients at risk of dying [61]. In a systematic review and meta-analysis of the prediction value of various biomarkers in 10,319 CAP patients, they demonstrated moderate-good accuracy to predict mortality but had no clear advantages over CAP-specific scores [62].…”
Section: Markers Of Prognosis Of Capmentioning
confidence: 99%